Which demographic quintile benefits from public health expenditure in Nigeria: A marginal benefit analysis - Ogujiuba Kanayo (Economies, 2022)
Policymakers concur that social investments are crucial, and that inequality must be decreased to accomplish long-term poverty reduction. Nigeria, one of the 20 poorest countries in the world, has a severely unequal society at the moment, with over 80% of the people living in deep, severe, and pervasive poverty, with an estimated 5% of the population possessing 85% of the country's resources. This article's focus is on how benefits are dispersed among various demographic groups. Previous data collection does not reflect the present realities of this topic. For this analysis, in southeast Nigeria, data sets from government agencies and for-profit service providers were utilized. The benefits of distinct quintiles were estimated using a marginal benefit incidence analysis. The results show that governmental spending in Nigeria is not pro-poor and that the country's southeast governments supported spending for the wealthy rather than the poor. The results show, among other things, that investment in health is not well directed; benefits from primary education and primary healthcare appear to be disproportionately dispersed to the upper class in the states studied, as they are throughout Nigeria. The paper serves as an example of the value of benefit incidence analysis (BIA). This article recommends effective targeted discretionary spending to lower systemic poverty and inequality. If education and health spending were more pro-poor, better education and health outcomes, strong governance, high per capita income, and wider access to information would all be more likely.
Keywords: A11; A13; G31; G32; G38; 330; expenditure; health; poverty